DISLOCATION GENERATION, SLIP SYSTEMS, AND DYNAMIC RECRYSTALLIZATION IN EXPERIMENTALLY DEFORMED PLAGIOCLASE SINGLE CRYSTALS - Stunitz H.; Fitz Gerald J.D.; Tullis J. (My University, 2003)
Three samples of gem quality plagioclase crystals of An60 were experimentally deformed at 900 °C, 1 GPa confining pressure and strain rates of 7.5-8.7x10-7 s-1. The starting material is effectively dislocation-free so that all observed defects were introduced during the experiments. Two samples were shortened normal to one of the principal slip planes (010), corresponding to a ''hard'' orientation, and one sample was deformed with a Schmid factor of 0.45 for the principal slip system [001](010), corresponding to a ''soft'' orientation. Several slip systems were activated in the ''soft'' sample: dislocations of the [001](010) and <110>(001) system are about equally abundant, whereas <110>{111} and [101] in (131) to (242) are less common. In the ''soft'' sample plastic deformation is pervasive and deformation bands are abundant. In the ''hard'' samples the plastic deformation is concentrated in rims along the sample boundaries. Deformation bands and shear fractures are common. Twinning occurs in close association with fracturing, and the processes are clearly interrelated. Glissile dislocations of all observed slip systems are associated with fractures and deformation bands indicating that deformation bands and fractures are important sites of dislocation generation. Grain boundaries of tiny, defect-free grains in healed fracture zones have migrated subsequent to fracturing. These grains represent former fragments of the fracture process and may act as nuclei for new grains during dynamic recrystallization. Nucleation via small fragments can explain a non-host-controlled orientation of recrystallized grains in plagioclase and possibly in other silicate materials which have been plastically deformed near the semi-brittle to plastic transition.
Keywords: DYNAMIC RECRYSTALLIZATION; DISLOCATIONS; SLIP SYSTEMS; PLAGIOCLASE DEFORMATION; FRACTURING; EXPERIMENTAL DEFORMATION